Modeling and Analysis of Thermal Elastohydrodynamic Lubrication Characteristic of Asymmetric Gear with a Small Number of Teeth - Deng Xianzhi (Jixie chuandong)
The asymmetric gear with a small number of teeth has the advantages of small size,large transmission ratio and high load capacity and so on,it is more and more widely used in various fields. Under good lubrication condition,the parameter change has important influence on the performance of thermal elastohydrodynamic lubrication characteristic of asymmetric gear with a small number of teeth,and has an important influence on the transmission efficiency and service life of gear. The model of asymmetric gear with a small number of teeth is built based on the Hertz contact theory and thermal elastohydrodynamic lubrication theory. The differential dispersion of the equation set is carried out through finite difference method,and by using the Newton-Raphson method,the Reynolds equation is solved to get complete numerical solution,the distribution of oil film pressure and film thickness are obtained. For solving EHL equations by overrelaxation iterative method,the thermal elastohydrodynamic lubrication characteristics in asymmetric gear with a small number of teeth meshing line of five special points are got,the change regulation of pressure angle,variable coefficient,between the load and the speed and the oil film thickness,pressure and temperature are analyzed. The results show that the maximum temperature appeared at the meshing point,the temperature of oil film at the nodes close to the steady state of lubricating oil temperature,and the change trend of the oil film temperature and oil film pressure is conformity.